The Image of the World in Children’s Speech: Concept of “Own” and “‘Strange’” - Romenkova, Valentīna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article presents the results of a study of the formation of a concept of ‘own’- ‘strange’ in pre-school age children. Perception of ‘own’-‘ strange’ in scientific studies is viewed in line with the characteristics of the concept sphere in several cultures, the influence of these perceptions on intercultural communication, and on maintaining positive self-image in a group with the inclusion of psychological defense. According to some authors ‘own’- ‘strange’ concept is one of the basic cultural and psychological oppositions that forms the cognitive value-assessment system of knowledge and reflects the uniqueness of perception and interpretation of the real world, due to the characteristics of the specific culture.